2014
DOI: 10.1192/bjp.bp.113.139014
|View full text |Cite
|
Sign up to set email alerts
|

Low birth weight, preterm birth and small for gestational age association with adult depression: systematic review and meta-analysis

Abstract: BackgroundThere is no consensus on the effects that low birth weight, premature birth and intrauterine growth have on later depression.AimsTo review systematically the evidence on the relationship of low birth weight, smallness for gestational age (SGA) and premature birth with adult depression.MethodWe searched the literature for original studies assessing the effect of low birth weight, premature birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 70 publications
6
55
0
Order By: Relevance
“…Our study did not reveal obvious predictors for the prevalence of depressive symptoms. In line with previous studies (Costello, ; de Mola, ), we found some signs of higher birth weight being associated with fewer depressive symptoms in adolescence. This may highlight the importance of intrauterine growth on later mental health.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study did not reveal obvious predictors for the prevalence of depressive symptoms. In line with previous studies (Costello, ; de Mola, ), we found some signs of higher birth weight being associated with fewer depressive symptoms in adolescence. This may highlight the importance of intrauterine growth on later mental health.…”
Section: Discussionsupporting
confidence: 93%
“…There may also be some characteristics in depression morbidity in low‐income countries that differ from those in the West. Most of the evidence of the association between early growth and depression comes from developed countries (Costello, , de Mola, ). It was not possible to investigate these potential differences in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Eight systematic reviews and meta-analyses have been published since the preterm behavioral phenotype was proposed in 2011 (8,12,17,20,(65)(66)(67)(68), each of which synthesizes the findings of between 6 and 74 studies, often with a single-outcome focus. However, they offer limited information on the nature of the phenotype.…”
Section: Gaps In the Preterm Behavioral Phenotypementioning
confidence: 99%
“…In 2013, preterm birth was the leading cause of both neonatal mortality (35% of 2.8 million deaths) and child mortality (17% of 6.3 million deaths) worldwide. Neonates born preterm are at increased risk of both short‐term complications, attributed to immaturity of multiple organ systems, and long‐term adverse health outcomes, such as neurodevelopmental disabilities, behavioral problems, childhood asthma, cardiovascular disease, diabetes and depression, in adult life. In addition, preterm birth is associated with a substantial economic cost and adverse psychosocial and emotional effects on families.…”
Section: Introductionmentioning
confidence: 99%